EMOTIONAL INTELLIGENCE AND SELF-PERCEPTION OF MEDICAL AND DENTAL STUDENTS OF PESHAWAR–PAKISTAN - Niazi, Aimen; Qayyum, Mahhum; Ikram, Zarmina; Sher, Somiyyah; Sethi, Mifrah Rauf; Irfan, Muhammad (Journal of Postgraduate Medical Institute, 2020)
Objective: To find out the relationship between emotional intelligence and self-perception of medical and dental students. Methodology: A cross sectional study was conducted in the medical and dental institutions of Peshawar-Pakistan from November 2018 to June 2019. Convenience sampling technique was used. Schutte Emotional Intelligence Scale (SEiS) and Self-Perception Profile (SPP) were used for this study. Data were analyzed using SPSS v.25. Independent sample t-test was applied to find the differences in emotional intelligence and self-perception in students based on gender, private/public sector institutions and medical/dental studies. Pearson correlation was used to find the relationship between SEiS, SPP and their subscales. Results: The mean age of the sample (n=1722) was 20.88 ±1.48 years. Majority of the students showed high level of emotional intelligence (n=959, 55.7%) while a total of 726 (42.2%) students showed high level of self-perception. Emotional intelligence was weakly correlated with self-perception (r =0.305). There was no significant difference between male and female students on emotional intelligence while female students showed significantly high level of self-perception (p =.000). Students of private sector showed high level of emotional intelligence (p =.034). Dental students showed significantly high level of self-perception (p =.001), whereas there was no significant difference between them on emotional intelligence (p =0.974). Conclusion: Emotional intelligence is weakly correlated with self-perception of the students. Female students had higher level of self-perception while private sector students had higher level of emotional intelligence.